Translation-dependent skin hyperplasia is promoted by type 1/17 inflammation in psoriasis - Xu, Rui; Li, Xiangyun; Huang, Xiaobao; Lin, Zhenjia; Xiong, Ying; Chen, Xiaohong; Chu, Coco; Han, Jiande; Wang, Fang (Journal of dermatological science, 2023)
Psoriasis vulgaris (PV) is a chronic skin inflammatory disease and characterized by aberrant epidermal hyperplasia. The molecule eukaryotic initiation factor (eIF) 4E controls translation initiation of certain protein synthesis and determines cell cycle or differentiation fate. To determine the role of eIF4E in keratinocytes abnormal differentiation in the context of psoriasis. The expression of eIF4E in psoriatic skin lesions and normal skin from human subjects was examined by western blot and immunohistochemistry. In a murine model of psoriasis-like dermatitis that is induced by topical imiquimod, 4EGI-1 was used to inhibit eIF4E activities. To measure murine skin eIF4E and keratinocytes differentiation, immunofluorescence and western blot assays were conducted. Normal human epidermal keratinocytes (NHEK) were isolated, cultured, and stimulated with cytokines including TNF-α, IFN-γ, and IL-17A, respectively. Immunofluorescence and western blot were performed to test eIF4E and effect of 4EGI-1 in a co-culture system. Compared with healthy controls, skin lesions from patients with PV exhibited a higher expression of eIF4E, which was positively correlated with the epidermal thickness. This expression pattern of eIF4E was replicated by the imiquimod-induced murine model. Skin hyperplasia and eIF4E activities in the murine model were attenuated by the administration of 4EGI-1. Both IFN-γ and IL-17A, rather than TNF-α, are sufficient to induce NHEK abnormal differentiation. This effect can be disrupted by 4EGI-1. eIF4E plays a crucial role in keratinocytes abnormal differentiation driven by type 1/17 inflammation in the context of psoriasis. The initiation of abnormal translation provides an alternative treatment target for psoriasis. •eIF4E, a key regulator of translation initiation, highly expressed in psoriasis.•Inhibition of eIF4E activities ameliorates IMQ-induced psoriasiform hyperplasia.•Typ1/17 inflammation promotes eIF4E activation in keratinocytes in vitro.•Abnormal translation initiation is a potential therapeutic target for psoriasis.